Identification of novel transcriptional regulators of PKA subunits in Saccharomyces cerevisiae by quantitative promoter-reporter screening - Pautasso, María Constanza (2016)
The cAMP-dependent protein kinase (PKA) signaling is a broad pathway that plays important roles in the transduction of environmental signals triggering precise physiological responses. However, how PKA achieves the cAMP-signal transduction specificity is still in study. The regulation of expression of subunits of PKA should contribute to the signal specificity. Saccharomyces cerevisiae PKA holoenzyme contains two catalytic subunits encoded by TPK1, TPK2 and TPK3 genes, and two regulatory subunits encoded by BCY1 gene. We studied the activity of these gene promoters using a fluorescent reporter synthetic genetic array screen, with the goal of systematically identifying novel regulators of expression of PKA subunits. Gene ontology analysis of the identified modulators showed enrichment not only in the category of transcriptional regulators, but also in less expected categories such as lipid and phosphate metabolism. Inositol, choline and phosphate were identified as novel upstream signals that regulate transcription of PKA subunit genes. The results support the role of transcription regulation of PKA subunits in cAMP specificity signaling. Interestingly, known targets of PKA phosphorylation are associated with the identified pathways opening the possibility of a reciprocal regulation. PKA would be coordinating different metabolic pathways and these processes would in turn regulate expression of the kinase subunits.